PELATIHAN MENGENAL POTENSI DIRI DAN KUALITAS PRIBADI BAGI SISWA SMK - Kartianti, Sahrestia; asgar, Sukitman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2021)
Self-understanding is important for every individual to understand himself realistically, both his strengths and weaknesses. The ultimate goal of self-understanding is to accept himself, himself as he is. Self-understanding is based on the existence of accurate and valid self-information. Accurate personal information will be used for consideration in self-direction, determination and decision making related to career or job that will be entered. Knowing your potential and personal qualities is very important in an effort to understand yourself, direct yourself and also develop yourself. The method used in this activity is to use the lecture method to present the material and exercises to the participants using instruments in the form of worksheets / assignments. Based on the results of these activities, it can be concluded that after participating in the training, students are able to recognize their own potential and personal qualities as seen from the level of understanding of 75%.